Effects of infill patterns on resistance-dependent strain and ammonia gas sensing behaviors of 3D-printed thermoplastic polyurethane modified with polypyrrole. Issue 17 (7th April 2022) - Kim, Yeon Jae; Choi, Jong Seob; Yim, Jin-Heong
Abstract : The role of geometrically distinct infill patterns of 3D-printed TPU modified with PPy was investigated. The performance of strain sensors and ammonia gas sensors made of TPU-PPy can be predicted more specifically by designing the infill patterns. Abstract : 3D printing technology has been significantly investigated over the past decade as a new way of building objects to increase the speed of design iteration and mass production. Infill patterning in the study of thermoplastic polyurethane (TPU) and conductive TPU composites in terms of mechanical and electrical properties is rarely investigated. In this work, different infill patterns (rhombus, square, and ladder) of 3D printed TPUs composited with polypyrrole (PPy) are prepared and evaluated. Vapor phase polymerization of PPy was performed for fabricating conductive TPU-PPy composites followed by simulated tensile stress distribution maps with respect to different infill patterns. Interestingly, the rhombus pattern showed uniform tensile stress distribution propagating in four directions under repetitive stretching while square and ladder patterns showed that stress distribution concentrated at specific areas. The uniform tensile stress distribution of rhombus patterns over 3D objects seems to contribute to less cracking and defect formation during repeated bending/releasing cycles, maintaining their molecular networks and superior mechanical and electrical properties without any loss. In addition, these different infill patterns of conductive TPUs were evaluated for resistance-dependent strain sensors as well as ammonia detection performance. The rhombus infill pattern showed effective strain sensor measurements while the ladder infill pattern showed effective characteristics in ammonia gas sensor evaluation. The performance of strain sensors and ammonia gas sensors fabricated by 3D printing and VPP can be predicted more specifically by designing the infill patterns.